Students’ Aesthetics Experience, Creative Self-Efficacy and Creativity: Is Creativity Instruction Effective? - Yuan-Cheng Chang (Journal of Educational Practice and Research, 2016)
Based on creativity component theory, creativity system theory and creative self-efficacy theory, this study aims to explore the influence of college students’ aesthetics experience and creative self-efficacy on their creativity and the role of creativity instruction as a mediator variable. The participants were 338 college design majors in 50 teams who were working on their graduation exhibitions, and 50 advising professors from departments related to design. Hierarchical Linear Models were applied for analysis. The result showed that instruction on enhancing students’ creative intention positively affect students’ aesthetics experience. Students’ aesthetics experience affects their creativity and creative self-efficacy. Creativity instruction with focus on creativity skills by means of promoting aesthetic attitude, aesthetic understanding, and offering complete experiences had a moderating effect on students’ perception toward creative product. However, there was a negative moderating effect of creative instruction on perceived aesthetic pleasure and students’ perception toward creative product. There was no moderating effect of creative instruction on the relationship between students’ creative self-efficacy and creativity. Accordingly, the study concluded that in order to enhance students’ creativity, universities should stress on the development of students’ aesthetics experiences and re-evaluation of approaches to creativity instruction.